Enhanced packet loss recovery for real time PC-based GigE vision AVI systems. (2015) - Taouil, Khaled; Jellad, Tarek; Chtourou, Zied
GigE vision could be a viable solution for seamless and cost effective integration of machine vision in manufacturing processes. Transmission delays, inherent to streaming and lost packets protocol implemented within the GigE, often jeopardise the implementation of networked PC-based machine vision. This is related to GigE vision open standard handling data integrity and error control through control and stream protocols (GVSP and GVCP) that implement data resend functions. In this work, we study the effect of data loss on the real time performance of distributed GigE vision AVI systems. We also introduce an optimised error recovery function based on definition of packets of interest (POIs) that allows for selective lost packet recovery based on their pertinence to subsequent machine vision processing. This scheme alleviates the traffic overhead by avoiding non-useful retransmissions. This mechanism allows reducing the latency and improving the predictability of such systems.